2018
DOI: 10.1186/s12864-018-4741-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of genes in soybean in response to Peronospora manshurica infection

Abstract: BackgroundSoybean downy mildew (SDM), caused by Peronospora manshurica (Pm), is a major fungal disease in soybean. To date, little is known regarding the defense mechanism at molecular level and how soybean plants response to Pm infection. In this study, differential gene expression in SDM-resistant (HR) and SDM-susceptible (HS) genotype was analyzed by RNA-seq to identify differentially expressed genes (DEGs) following Pm infection.ResultsOf a total of 55,017 genes mapped to the soybean reference genome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…4 A). Similar observations were found in soybean during Peronospora manshurica infection ( Dong et al, 2018 ), which may be due to stronger signals as a result of bacterial invasion. Also, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…4 A). Similar observations were found in soybean during Peronospora manshurica infection ( Dong et al, 2018 ), which may be due to stronger signals as a result of bacterial invasion. Also, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…This hypothesis is supported by the recent publication by Dong et al. (2018) that identified the differential expression of genes and GO categories related to ion homeostasis in the resistant response to soybean downy mildew ( Peronospora manshurica) , suggesting that modification of nutrient availability plays a vital role in the defense response.…”
Section: Discussionmentioning
confidence: 61%
“…Despite VGGRU-1 and VRM (Gg) 1 having different MYMV infection responses, 275 common DEGs were found in both mungbean genotypes. Previous studies have shown the advantage of focusing on the common DEGs between the resistant and susceptible genotypes to discover the possible candidate resistance genes in various diseases [15,22]. Therefore, we were mainly focused on 275 common DEGs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, transcriptome comparisons among resistant and susceptible genotypes to pathogens in various crops, including mungbean [19], urdbean [20,21], soybean [22,23], rice [24,25], and tomato [16] extended our knowledge on the genes and mechanisms underlying the resistance to plant pathogens. In regard to the available literature information, RNA-Seq has yet to be used to investigate the transcriptome response of mungbean to MYMV.…”
Section: Introductionmentioning
confidence: 99%